4D printed origami metamaterials with tunable compression twist behavior and stress-strain curves. (15th November 2020) - Tao, Ran; Ji, Longtao; Li, Ying; Wan, Zhishuai; Hu, Wenxia; Wu, Wenwang; Liao, Binbin; Ma, Lianhua; Fang, Daining
Abstract: Origami has received significant interest from the science and engineering community as a design method and used to construct expandable mechanical metamaterials by folding and unfolding along the crease line. Here, we adopted a 4D printing method with shape memory polymer to create a smart origami metamaterial with tunable stress-strain curves, controllable compression twist deformation, shape programming and self-expansion, and develop its deformation theory model. The effects of unit structure parameters and temperature field on the mechanical properties and functional deformation of the metamaterial are analyzed using experiments, theory model and finite element method. The origami structure can realize the shape programming, self-expansion and mechanically tunable by control temperature, and switch between monostability and bistability by adjusting the parameters. The structure parameters, temperature field, and series combination method are used to adjust and control the stress-strain curves and compression twist deformation behavior of the metamaterials. This multifunctional metamaterial may find a wide range of applications, such as, mechanical storage, tunable shock absorption interface and soft robots.